2021
DOI: 10.2174/1871530320666200628025430
|View full text |Cite
|
Sign up to set email alerts
|

Ruta Montana Evokes Antihypertensive Activity Through an Increase of Prostaglandins Release in L-NAME-Induced Hypertensive Rats

Abstract: Aims: The aim of the study was to investigate experimentally the antihypertensive effect of Ruta Montana. Background: Ruta montana L. is traditionally used in Moroccan herbal medicine to treat hypertension. This study aimed to evaluate experimentally the hypotensive and vasoactive properties of this plant. Objective: The objective of the study was to evaluate the effect of the aqueous extract of Ruta Montana on blood pressure parameters in LNAME-induced hypertensive rats and to determine the vasorelaxant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Indomethacin, a potent inhibitor of COX-1 and COX-2, inhibits the synthesis of prostaglandins. Previous literature reported that prostaglandins such as prostacyclin (PGI2) reduce blood pressure by increasing the level of cAMP leading to vasorelaxation and, ultimately, hypotension [ 8 , 9 ]. As in our study, indomethacin blocked the hypotensive effects of pulegone in rats, indicating that COX pathways may be involved in the hypotensive effect seen with pulegone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indomethacin, a potent inhibitor of COX-1 and COX-2, inhibits the synthesis of prostaglandins. Previous literature reported that prostaglandins such as prostacyclin (PGI2) reduce blood pressure by increasing the level of cAMP leading to vasorelaxation and, ultimately, hypotension [ 8 , 9 ]. As in our study, indomethacin blocked the hypotensive effects of pulegone in rats, indicating that COX pathways may be involved in the hypotensive effect seen with pulegone.…”
Section: Discussionmentioning
confidence: 99%
“…PGI2, primarily COX-2 derived, is a vasodilator expressed mainly by endothelial and vascular smooth muscle cells. It reduces blood pressure by increasing the level of cAMP, which leads to vasorelaxation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it caused dose-dependent relaxation of the aorta. It is likely that the prostaglandin pathway mediates these processes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many in vitro and in vivo works have shown that RM, especially its EOs, exhibit various biological activities such as antibacterial (11,(16)(17)(18)(19)(20), antifungal (11,16,(20)(21)(22), antioxidant (11,16,(23)(24)(25), antidiabetic (26), anticancer (24), anti-fertility (27), antihypertensive (28), insecticidal, and larvicidal properties (29,30).…”
Section: Introductionmentioning
confidence: 99%